Electronic properties of AlN crystal doped with Cr, Mn and Fe - Syrotyuk, S.V.; Shved, V.M. (Condensed Matter Physics, 2013)
The spin-resolved electronic energy band spectra, as well as partial and total density of electronic states of the crystal AlN, doped with Cr, Mn and Fe, have been evaluated within the projector augmented waves (PAW) approach by means of the ABINIT code. The Hartree-Fock exchange for correlated electrons is used to describe the correlated orbitals in the PAW framework. The calculated one-electron energies for electrons of spin up and down are very different. We have found that all the considered crystals are ferromagnetic. Залежнi вiд спiна електроннi енергетичної спектри, а також парцiальнi й повнi щiльностi електронних станiв кристала AlN, легованого Cr, Mn та Fe, були отриманi за методом проекцiйних парцiальних хвиль (PAW) за допомогою програми ABINIT. Обмiнний потенцiал Хартрi-Фока для скорельованих електронiв використовується для опису скорельованих орбiталей в рамках PAW. Розрахованi одноелектроннi енергiї для електронiв зi спiном вгору i вниз є дуже рiзнi. Ми виявили, що всi розглянутi кристали є феромагнетиками.